2011
DOI: 10.3109/02699052.2011.607782
|View full text |Cite
|
Sign up to set email alerts
|

Robotic gait training in patients with impaired consciousness due to severe traumatic brain injury

Abstract: The study showed that robotic gait training induced measurable changes in the EEG power spectrum in healthy individuals, while no changes were observed in patients with severe TBI. The absence of the EEG changes following training might be an indicator of the severity of brain dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The effect of robotic gait training on consciousness has not been studied as intensively. Lapitskaya et al [16] were unable to find an effect of a single session of robotic gait training on consciousness of individuals with severe traumatic brain injury and suspected that the reason was the severity of brain dysfunction in their patient sample.…”
Section: Early Therapy Onsetmentioning
confidence: 99%
“…The effect of robotic gait training on consciousness has not been studied as intensively. Lapitskaya et al [16] were unable to find an effect of a single session of robotic gait training on consciousness of individuals with severe traumatic brain injury and suspected that the reason was the severity of brain dysfunction in their patient sample.…”
Section: Early Therapy Onsetmentioning
confidence: 99%
“…A systematic review from 2011 reported 10 randomized controlled trials for the use of robotic devices in CVA rehabilitation, but none for TBI (Tomida et al, 2019 ). However, recent reports indicate increased use of robotic rehabilitation following TBI; for example, to quantify the degree of impairment (Logan et al, 2018 ), improve cognitive function (Maggio et al, 2020 ), to support treadmill training (Esquenazi et al, 2013 ), to measure brain activity while having robotic gait training (Lapitskaya et al, 2011 ), and to increase gait velocity (Esquenazi et al, 2017 ). While the outcomes of these studies are mixed due to the differences in patient population, training techniques used, and type of equipment, it is promising that the field is recognizing how robotics present with a novel opportunity to improve quality of life in patients with TBI.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review from 2011 reported ten randomized controlled trials for the use of robotic devices in CVA rehabilitation, but none for TBI 27 . However, recent reports indicate increased use of robotic rehabilitation following TBI; for example, to quantify the degree of impairment 28 , improve cognitive function 29 , to support treadmill training 30 , to measure brain activity while having robotic gait training 31 , and to increase gait velocity 32 . While the outcomes of these studies are mixed due to the differences in patient population, training techniques used, and type of equipment, it is promising that the eld is recognizing how robotics present with a novel opportunity to improve quality of life in patients with TBI.…”
Section: Discussionmentioning
confidence: 99%